Perencanaan Kawasan Wisata Edukasi Mangrove Tanjung Batu, Sekotong Tengah - Andi Chairil Ichsan; Irwan Mahakam Lesmono Aji; Maiser Syaputra; Diah Permata Sari; Wihelmus Jemarut; Kornelia Webliana (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Abstract: The establishment of educational tourism in mangrove areas is expected to prevent and overcome the impact of tourist activities on nature and culture. This community service activity was carried out in the Tanjung Batu Mangrove area, Sekotong Village with the aim of designing an educational tourism concept to maximize the use of mangroves as a new tourist attraction in the Central Sekotong area. The selection of mangrove locations was carried out by purposive sampling, and the methods applied to this service were observation, socialization, discussion and direct area arrangement. The results of observations showed the potential flora in Tanjung Batu, namely Rhizophora mucronata, Rhizophora stylosa and Avicennia lanata. Meanwhile, the birds types found in this area are terns, swallows, black eagles, sparrows, king prawns and Asian plover. The potential of flora and fauna is then described in the Flora-Fauna interpretation board and a short documentary related to the area which was prepared jointly by the manager and the community service team. Recommendations for the types of educational tourism activities that can be offered for the Tanjung Batu Mangrove area, namely bird watching, mangrove planting, canoeing, and making mangrove films. Keywords: Mangrove, Tanjung Batu, Educational tourism